2020
DOI: 10.1103/physrevc.102.014319
|View full text |Cite
|
Sign up to set email alerts
|

β -delayed fission of isomers in Bi188

Abstract: β-delayed fission (βDF) decay of a low-spin (ls) and a high-spin (hs) isomer in 188 Bi was studied at the ISOLDE facility at CERN. Isomer-selective laser ionization and time gating were employed to investigate each isomer separately and their βDF partial half-lives were determined: T 1/2p,βDF (188 Bi hs) = 5.6(8) × 10 3 s and T 1/2p,βDF (188 Bi ls) = 1.7(6) × 10 3 s. This work is the first βDF study of two states in one isotope and allows the spin dependence of low-energy fission to be explored. The fission fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The Gamow-Teller response of even and odd 90−94 Zr isotopes [16] and β − -decay of 83 Ga [34] have also been successfully studied within the same approach. In the same framework, β + and electron-capture (EC) decay rates have been estimated for 188 Bi [35]. In the present study, we follow the same approach and estimate the β + and EC decay half-lives of 182,184,186 Hg isotopes to choose between the oblate or prolate configurations.…”
Section: B Even Hg Isotopesmentioning
confidence: 99%
“…The Gamow-Teller response of even and odd 90−94 Zr isotopes [16] and β − -decay of 83 Ga [34] have also been successfully studied within the same approach. In the same framework, β + and electron-capture (EC) decay rates have been estimated for 188 Bi [35]. In the present study, we follow the same approach and estimate the β + and EC decay half-lives of 182,184,186 Hg isotopes to choose between the oblate or prolate configurations.…”
Section: B Even Hg Isotopesmentioning
confidence: 99%
“…Two predominantly α-decaying states are known in 188 Bi: the 1 (+) ground state (gs) based on the presumed π 1/2 − [530] f 7/2 ⊗ ν1/2 − [521]p 3/2 configuration [5,8], and the (10 − )isomerfromtheπ h 9/2 ⊗ νi 13/2 coupling [9]. Based on laser-spectroscopy studies [5], the 1 (+) gs was found to be strongly prolate deformed with β =+0.25 (7), whereas the (10 − ) isomer is nearly spherical.…”
Section: Introductionmentioning
confidence: 99%